Podoplanin Positive Myeloid Cells Promote Glioma Development by Immune Suppression - Eisemann, Tanja; Costa, Barbara; Peterziel, Heike; Angel, Peter (Frontiers in oncology, 2019)
The dynamic and interactive tumor microenvironment is conceived as a considerable parameter in tumor development and therapy response. Implementing this knowledge in the development of future cancer treatments could provide novel options in the combat of highly aggressive and difficult-to-treat tumors such as gliomas. One compartment of the tumor microenvironment that has gained growing interest is the immune system. As endogenous defense machinery the immune system has the capacity to fight against cancer cells. This, however, is frequently circumvented by tumor cells engaging immune-regulatory mechanisms that disable tumor-directed immune responses. Thus, in order to unlock the immune system against cancer cells, it is crucial to characterize in great detail individual tumor-associated immune cell subpopulations and dissect whether and how they influence immune evasion. In this study we investigated the function of a tumor-associated myeloid cell subpopulation characterized by podoplanin expression on the development of high-grade glioma tumors. Here, we show that the deletion of podoplanin in myeloid cells results in increased (CD8(+)) T-cell infiltrates and significantly prolonged survival in an orthotopic transplantation model. In vitro co-cultivation experiments indicate a podoplanin-dependent transcriptional regulation of arginase-1, a well-known player in myeloid cell-mediated immune suppression. These findings identify podoplanin positive myeloid cells as one novel mediator of the glioma-induced immune suppression. Thus, the targeted ablation of podoplanin positive myeloid cells could be included in combinatorial cancer therapies to enhance immune-mediated tumor elimination.
Gesehen am 28.05.2019